DEVELOPING ECONOMY OF INFORMATION SOCIETY IN RUSSIA - Oleg E. Kalenov (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
Today we can observe the trend of the rising role of knowledge and intangible assets, which is stipulated by the new stage of economic development, i.e. economy of information society. The issue of the information society development is directly connected with technological innovation. The article shows the essence of information society, its principle determining factors, including human capital, innovation potential, informationcommunication infrastructure, information security, information environment, etc. The author analyzes dynamics of these factors in our country and makes international comparisons. It brings us to the conclusion that Russia is lagging behind the world leaders by key indicators. Apart from that, developing economy of information society in our country is mainly identified with the use of information technologies without taking into account social components. It is underlined that the essential role in this process should be attributed to institute of trust. The author puts forward the hypothesis about future changes in economy and society, in production processes and in man himself and proposes a set of steps aimed at intensifying the process of developing economy of information society in the country and discusses the related prospects.